Pemanfaatan Pupuk Organik Cair Limbah Buah-Buahan dengan Metode Tetes terhadap Pertumbuhan Tanaman Kailan - Sri Rahayu, Yekti; Rositawati, Ratna; Hadija, Yasinta (Folium : Jurnal Ilmu Pertanian, 2024)
The level of effectiveness of organic fruit waste used as organic fertilizer is not yet known. This research was carried out to test the use of liquid organic fertilizer derived from fruit peel waste (pineapple, banana and the addition of Tithonia diversifolia leaves) on the growth and yield of kailan plants. The research design used was a Randomized Block Design which consisted of eleven POC concentration treatments (composition of POC and water) and was repeated three times. Data on plant growth and yield parameters were analyzed variance at the 5% level, and if there was a significant effect, the Least Significant Difference Test was continued at the 5% level. The results showed that the application of fruit waste POC with compositions ranging from 20 ml POC + 80 ml water (P2) to 65 ml POC + 35 ml water (P8) provided growth in plant height, number of leaves, leaf area and the fresh weight of the plant is better until harvest at 12 days after planting. Providing increasingly concentrated fruit waste POC of 70 ml + 30 ml water (P9) to 75 ml + 25 ml water (P10) reduces the fresh weight of the crop